2007
DOI: 10.1002/ab.20173
|View full text |Cite
|
Sign up to set email alerts
|

Changes in attitudes towards war and violence after September 11, 2001

Abstract: Two inter-related studies examined the effect of the September 11, 2001, terrorist attacks on attitudes towards war and violence. A three-wave between-subjects analysis revealed that attitudes towards war became more positive after September 11, 2001 and remained high over a year afterwards. Self-reported trait physical aggression also rose after September 11. Attitudes towards penal code violence (PCV) became more positive immediately after September 11, but were somewhat reduced a year afterward. A two-wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 69 publications
1
36
1
2
Order By: Relevance
“…For example, Camagey and Anderson (2007) found that attitudes toward war became more positive after 9/11 and remained high over a year later. Support for violence as part of the penal code becatne more positive immediately after 9/11 but was not sustained over time.…”
Section: Terrorism and Social And ' Political Attitudesmentioning
confidence: 95%
“…For example, Camagey and Anderson (2007) found that attitudes toward war became more positive after 9/11 and remained high over a year later. Support for violence as part of the penal code becatne more positive immediately after 9/11 but was not sustained over time.…”
Section: Terrorism and Social And ' Political Attitudesmentioning
confidence: 95%
“…Participants were asked to indicate the extent to which they agree or disagree with these statements, assessed on a 5-point Likert-type scale (1= strongly disagree, 5=strongly agree). This scale successfully predicted self-reported violent behavior and self-reported trait aggression, anger, and hostility (Carnagey & Anderson, 2007).…”
Section: Procedures and Materialsmentioning
confidence: 97%
“…Nevertheless, the GAM has also provided useful findings for understanding changes in violent attitudes toward war (Carnagey & Anderson, 2007), the effect of attention and impulsivity problems in aggressive behavior (Swing & Anderson, 2014), and even the relationship between personality and aggression (Barlett & Anderson, 2012;Housie, Gilbert, Simpson, & Daffern, 2013).…”
Section: General Aggression Modelmentioning
confidence: 99%